2011
DOI: 10.1111/j.1365-2648.2010.05546.x
|View full text |Cite
|
Sign up to set email alerts
|

Incentives and barriers to lifestyle interventions for people with severe mental illness: a narrative synthesis of quantitative, qualitative and mixed methods studies

Abstract: Healthcare professionals, in particular nurses, should consider issues that may hinder or encourage individuals in this clinical group to participate in lifestyle interventions if the full benefits are to be achieved. Further research is needed to explore possible incentives and barriers from the service users' own perspective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
168
2
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(188 citation statements)
references
References 59 publications
16
168
2
1
Order By: Relevance
“…32 Second, families indicated that primary barriers to participation in or completion of a behavioral weight loss program were mostly related to psychiatric diagnosis or symptoms, as has been reported in adult mentally ill populations. 20,21,33 Caregivers also frequently cited a preference for in-session support to expose the child to new foods and PAs. Finally, pragmatic challenges with time management, costs, and transportation were cited as common barriers to participating in treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…32 Second, families indicated that primary barriers to participation in or completion of a behavioral weight loss program were mostly related to psychiatric diagnosis or symptoms, as has been reported in adult mentally ill populations. 20,21,33 Caregivers also frequently cited a preference for in-session support to expose the child to new foods and PAs. Finally, pragmatic challenges with time management, costs, and transportation were cited as common barriers to participating in treatment.…”
Section: Discussionmentioning
confidence: 99%
“…20,21 Programming that increases health knowledge and that offers social engagement and daily structure is cited as promoting engagement in behavioral weight loss programs. 22 There have been no published reports of behavioral weight loss interventions in antipsychotic treated youth, and no data are available regarding the preferences for and barriers to participating in behavioral weight loss interventions in this uniquely at-risk population. However, studies of barriers to participation in and preferences for weight loss treatment in non-mentally ill obese youth can offer useful information.…”
mentioning
confidence: 99%
“…Qualitative research by several authors (Gorczynski et al, 2013;Leutwyler et al, 2013;Roberts and Bailey, 2013) has highlighted important findings which provided a deeper understanding of the experiences and challenges faced by people with schizophrenia trying to engage in physical activity. Further, previous reviews (Roberts and Bailey, 2011;Soundy et al, 2012) have identified the value of including rich qualitative data in order to further understanding within this domain of research. However, these reviews did not attempt to combine the views of HCPs with patients' experiences of physical activity.…”
Section: Introductionmentioning
confidence: 99%
“…Healthcare professionals, in particular master’s level mental health nurses, need to consider matters that may hinder or encourage individuals with mental health issues to participate in lifestyle interventions to achieve sufficient benefits (Roberts & Bailey, 2011). Simple measures may reduce potential barriers and improve participation in lifestyle interventions (Robson & Gray, 2007).…”
Section: Skillsmentioning
confidence: 99%
“…Support regarding lifestyle changes can focus on strengthening the person’s self-efficacy based on the person’s own experiences, as the meaning of lifestyle changes can be understood as a person’s internal and external endeavours, to make well-considered decisions (Lundström, Hedman Ahlström, & Jormfeldt et al, 2017). Thus, it may be crucial to emphasize a moderate intervention level that facilitates participation and social interactions among group members to perceive oneself as a capable person (Roberts & Bailey, 2011). Nurse-based physical healthcare in mental health services is in its early stages (Happel, Platania-Phung, & Scott, 2014a), and master’s level mental health nurses have an important task to assist service users to understand and verbalize potential physical health risks, and to find out what motivates them to adopt health behaviours (Hultsjö & Syrén, 2013).…”
Section: Skillsmentioning
confidence: 99%